Overview of Work Fatigue in Workers at Toyota Kombos Workshop in Manado City - Yessie Angelika Simatupang; Jeini Ester Nelwan; Sri Seprianto Maddusa (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The prevalence of work-induced fatigue reaches around 32% of workers globally. In Indonesia, fatigue is a contributor to work accidents recorded as many as 162,327 cases of work accidents and 358 cases of which were recorded in North Sulawesi. Workshop workers are prone to experiencing work fatigue due to the demands of work involving work activities, work environment conditions that do not meet ergonomic principles, forced work postures, repetitive and monotonous nature of work, insufficient energy intake, quality of rest time during working hours and pressure of service completion timevehicle. This study aims to find out the picture of work fatigue in workers at the Toyota Kombos workshop in Manado City. The design of this study is quantitative descriptive with a cross sectional approach on 43 respondents which is the total number of workshop workers selected using total sampling. Data were collected through interviews using the Work Fatigue Sentiment Questionnaire (KAUPK2) and then analyzed univariately to see the distribution of work fatigue. Mild work fatigue was more commonly found at the age level of 26-35 years, high school education level/equivalent, no history of illness, long working period (≥ 5 years), male, and mechanical/technician respondents. Research shows that the majority of workshop workers experience mild fatigue, which is 79.1% of respondents, workers who experience moderate fatigue are 7% of respondents, while other workers are in normal conditions, which is 13.9%. And in this study, no severe fatigue was found.